First‐ and second‐trimester uterine artery pulsatility index as a combination factor in predictive diagnosis of pregnancy‐induced hypertension. Issue 3 (2nd March 2021) - Dash, Sonali S.; Jena, Pramila; Khuntia, Swetaparna; Pathak, Mona; Rath, Sudhanshu K.
Abstract: Objective: Hypertensive disorder of pregnancy is a major cause of fetal and maternal morbidity and mortality. The current approach for pregnancy‐induced hypertension (PIH) screening is complex and expensive. The present prospective cohort study assesses the advantage of combining first‐ and second‐trimester uterine artery pulsatility index (UAPI) for predictive diagnosis of PIH. Methods: A total of 151 prenatal cases in their first trimester were studied and followed up till delivery. The mean UAPI was calculated for the first and second trimesters during the nuchal translucency and anomaly scans. Receiver operating characteristic analysis was used to calculate the cut‐off of UAPI for first‐trimester, second‐trimester, and both trimesters combined. Results: Twenty‐seven (17.9%) pregnant women developed PIH. Mean ± SD UAPI values for first and second trimesters were 1.92 ± 0.60 and 1.23 ± 0.36, respectively. The cut‐offs for abnormal UAPI were ≥2.51, ≥1.32, and ≥1.91 for first trimester, second trimester, and both trimesters combined, respectively. The sensitivity and specificity of UAPI in predictive diagnosis of PIH were 82% and 95% for first trimester, 93% and 85% for the second trimester, and 93% and 98% for both trimesters combined. Conclusion: Combining UAPI of first and second trimesters improves the predictive diagnosis of PIH, which can be carried out during the nuchal translucency and anomaly scans without imparting extra cost to the patient. Synopsis: Combining uterine artery pulsatility index in the first and second trimester can be a simple and cheap alternative for the screening of pregnancy‐induced hypertension.